Desenvolvimento Sustentável: uma análise das limitações do índice de desenvolvimento humano para refletir a sustentabilidade ambiental - Martins, Ana Raquel Paiva (2006)
The concept of sustainable development was spread out mainly through the studies carried through for the Commission of Bründtland in 1986. The objective of was to conciliate economic development with the environment. In this trajectory, it had also the concern in the form to measure the development, not only for the increase of the income, but also for the quality of life of the people. With this intention, in 1990, the first version of the Human Development Index (HDI) was created. Currently, the society, with the incorporation of the ambient concern, needs indicators that reflect the quality of life on the present, but also if it is possible to keep it in the future. In this direction, this study presented some of the indicators of sustainable development and chose the Environmental Sustainability Index (ESI) to make a comparison with the HDI. The objective of the comparison was to present the existing limits in the HDI to reflect the development sustainable. In the quantitative analysis of the data, it was demonstrated that the Human Development Index is not capable alone to reflect the questions that involve the human development and the environment. With intention to incorporate an ambient dimension, it was added in the HDI, the ESI, creating itself the Hybrid Human Development Index (HDIh). The new indicator demonstrated to the fragilities of the HDI front to the questions that involve the sustainable development, where the man s quality of life has to be lined up with the preservation of the nature.